Password Data Authentication Using a Combination of MD5 and Playfair Cipher Matrix 13x13 - Bayu Priyatna; April Lia Hananto (Information System; Universitas Buana Perjuangan Karawang, 2020)
Data security and confidentiality are the most important things that must be considered in information systems. To protect the cryptographic algorithm reliability it uses. MD5 is one technique that is widely used in password data security issues, which algorithm has many advantages including. MD5 has a one-way hash function so that the message has been converted to a message digest, and it is complicated to restore it to the original message (plaintext). In addition to the advantages of MD5 also has a variety of shortcomings including; very easy to solve because MD5 has a fixed encryption result, using the MD5 modifier generator will be easily guessed, and MD5 is not proper because it is vulnerable to collision attacks. The research method used in this study uses Computer Science Engineering by conducting experiments combining two cryptographic arrangements. The results obtained from this study after being tested with Avalanche Effect technique get ciphertext randomness results of 43.69%, which tends to be very strong to be implemented in password data authentication.